A Flexible Hydrogen‐Bonded Organic Framework Constructed from a Tetrabenzaldehyde with a Carbazole N−H Binding Site for the Highly Selective Recognition and Separation of Acetone. (22nd November 2022) - Chen, Liangji; Yuan, Zhen; Zhang, Hao; Ye, Yingxiang; Yang, Yisi; Xiang, Fahui; Cai, Kaicong; Xiang, Shengchang; Chen, Banglin; Zhang, Zhangjing
Abstract: Rational design of hydrogen‐bonded organic frameworks (HOFs) with multiple functionalities is highly sought after but challenging. Herein, we report a multifunctional HOF (HOF‐FJU‐2 ) built from 4, 4′, 4′′, 4′′′‐(9H‐carbazole‐1, 3, 6, 8‐tetrayl)tetrabenzaldehyde molecule with tetrabenzaldeyde for their H bonding interactions and carbazole N−H site for its specific recognition of small molecules. The Lewis acid N−H sites allow HOF‐FJU‐2 facilely separate acetone from its mixture with another solvent like methanol with smaller p K a value. The donor (D)‐π‐acceptor (A) aromatic nature of the organic building molecule endows this HOF with solvent dependent luminescent/chromic properties, so the column acetone/methanol separation on HOF‐FJU‐2 can be readily visualized. Abstract : Combining tetrabenzaldeyde for hydrogen bonding interactions, a carbazole N−H site for the specific recognition of small molecules, and a D‐π‐A building molecule for solvent‐dependent chromic properties has led to the hydrogen‐bonded organic framework HOF‐FJU‐2. This combination has enabled the separation of an acetone/methanol mixture to be readily visualized.